Analyzing students’ science process skills through mobile learning using virtual laboratory - Aida Fikriyah; Mochammad Ahied (Biosfer: Jurnal Pendidikan Biologi, 2022)
Science process skills have to be taught during learning process in order students are able to develop their skills in examining and solving science problems by leading such investigation process in which are beneficial for their future life. This study aims at analyzing students’ science process skills in the concepts of biodiversity through mobile leaning using virtual laboratory. The research included in a descriptive quantitative study. The mobile learning was conducted on November 2021 toward 24 students from 7th grade in a junior high school. Students learned the concepts of biodiversity through virtual laboratory in which the virtual laboratory has been already stated as valid and appropriate to be implemented in the learning process. In addition, the students’ science process skills were evaluated and measured using a test. Findings indicated that the students’ science process skills is 60.42±8.59. Therefore, it can be concluded that students’ science process skills reached moderate through mobile learning using virtual laboratory.